Sarcoidosis: Is It a Possible Trigger of Inclusion Body Myositis? - Ali Zakaria; Issam Turk; Kenneth Leung; Ana Capatina-Rata; Waseem Farra (Case Reports in Rheumatology)
Sarcoidosis is a multisystem disorder of unknown etiology, characterized pathologically by the presence of nonnecrotizing granulomatous inflammation in affected organs. Although skeletal muscle is involved in 50–80 percent of individuals with sarcoidosis, symptomatic myopathy has been shown to be a rare manifestation of the disease. Inclusion body myositis (IBM) is a rare acquired idiopathic inflammatory myopathy with the insidious onset of asymmetric and distal muscle weakness that characteristically involves the quadriceps, tibialis anterior, and forearm flexors. Moreover, dysphagia can be the presenting complaint in one-third of patients. Herein, we are presenting a case of 67-year-old African American female who presented with one-month history of new onset progressive dyspnea on exertion. She was diagnosed with stage IV sarcoidosis based on chest CT scan findings and transbronchial lung biopsy revealing nonnecrotizing granulomatous inflammation. Over the next three months after her diagnosis, she presented to the hospital with progressive dysphagia associated with asymmetrical distal muscle weakness. A quadriceps muscle biopsy revealed features consistent with inclusion body myositis. We are reporting this case as it may support the hypothesis of sarcoidosis being a trigger that possibly promotes the development of inclusion body myositis, leading to a very poor prognosis.